Ein Looking at You : Kunst - Provokation - Unterhaltung - Video. - Berger, Tobias; Block, René; Bradley, Slater; Bärthel, Regina; Glaser, Martin; Gripp, Stephan; Gröting, Asta; von Haken, Boris; Heinrich, Barbara; Jonas, Joan; Land, Peter; Liesbrock, Heinz; et al. (Kassel : Kunsthalle Fridericianum, 2001)
Alys, Francis ; Ashley, Robert ; Böhm, Simone ; Böhmler, Claus ; Bradley, Slater ; Breitz, Candice ; Cardiff, Janet ; Erkmen, Ayse ; Fox, Terry ; Gröting, Asta ; Husain, Oliver ; Huyghe, Pierre ; Jankowski, Christian ; Jonas, Joan ; Kairiss, Viesturs ; Kim, Soo-Ja ; Kyupi Kyupi ; Land, Peter ; Logue, Joan ; Marclay, Christian ; Melikian, Nathalie ; Paik, Nam June ; Pakalniña, Laila ; Santos, Carles ; Semper, Ene-Liis ; Sorin, Pierrick ; Spitzer, Serge ; Wallinger, Mark ; Wegman, William
Looking at You : Kunst - Provokation - Unterhaltung - Video, Kunsthalle Fridericianum, Kassel, 12.8. bis 16.9.2001
Duits
kunstcatalogus